PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN KREATIVITAS TERHADAP MINAT BERWIRAUSAHA - Cendyta, Gloria Patri; Novaria, Rachmawati; Andayani, Sri (Universitas 17 Agustus 1945 Surabaya, 2019)
This study aims to determine the effect of Entrepreneurship and Creativity Education variables on Entrepreneurial Interest partially, simultaneously and dominating variables. The method used in this study is quantitative research using multiple linear regression analysis methods. Students of the Faculty of Social and Political Sciences of the University of August 17, 1945 who are still actively studying (class of 2016 - 2017) and have taken Entrepreneurship courses into the population in this study were 239 students. The number of samples obtained as many as 150 students was calculated using purposive sampling technique. The data collection technique used is the distribution of questionnaires / questionnaires.This study resulted in (1) Partially showing a positive influence between entrepreneurship education variables on the interest in entrepreneurship in students of the University of Surabaya's Faculty of Social and Political Sciences August 17, 1945. (2) The variable of creativity also has a positive effect on the interest in entrepreneurship in the students of the Faculty of Social and Political Sciences of the University of Surabaya, August 17, 1945. (3) Simultaneously also shows that between entrepreneurship education and creativity together have a positive effect on the interest in entrepreneurship in the students of the Faculty of Social and Political Sciences, University of Surabaya, August 17, 1945. Keywords: Entrepreneurship Education, Creativity, and Entrepreneurship Interest.